A Composite Photocatalyst for Methylene Blue Degradation Under Visible Light Irradiation - Jalal Samed, Ahmed; Hasnat, M.A.; Machida, Masato (Asian Journal of Chemistry, 2014)
A new composite phocatalyst Mn1-xCdxS (x = 0.18) has been introduced, which can efficiently degrade methylene blue even under ordinary visible light. The order of reactivity, irrelevant to the nature of light, followed the order of Mn1-xCdxS (x = 0.18) > TiO2 > ZnO > CdS at neutral pH. The lower band gap energy (2.1 eV) of the catalyst Mn1-xCdxS (x = 0.18) was identified as the reason of the higher reactivity.